Conceptual Analysis of al-Qirā’ah in Arabic Language Learning at the Higher Education Level | Analisis Konseptual al-Qirā’ah dalam Pembelajaran Bahasa Arab pada Perguruan Tinggi - Restian Meiza Putri; Muhammad Syaifullah; Ammar Zainuddin (NAJAH BESTARI, 2025)
Reading skills (al-Qirā’ah) constitute one of the principal pillars in mastering the Arabic language, especially within the context of higher education, which requires students to understand various types of texts critically and analytically. Numerous studies affirm that text comprehension ability is influenced by linguistic, cognitive, and pedagogical factors, as well as appropriate learning strategies. At the university level, reading instruction cannot merely emphasize basic linguistic aspects; rather, it must integrate academic competencies such as discourse analysis and critical comprehension. This aligns with the views of Carrell and Grabe, who emphasize that reading in a foreign language requires the activation of schemata along with the simultaneous application of top-down and bottom-up strategies. In Arabic language learning, al-qirā’ah is not only understood as the technical ability to pronounce letters and words, but as a complex linguistic and cognitive process. This process involves the ability to understand grammatical structures, lexical meanings, pragmatic contexts, and the capacity to connect textual information with the reader’s prior knowledge. This article aims to provide a comprehensive conceptual analysis of al-Qirā’ah in Arabic language instruction at the university level, with particular attention to foundational reading theories, pedagogical approaches, and the practical challenges encountered in implementation. Universities generally employ intensive reading methods (Qirā’ah Jahrīyah / Qirā’ah Mukhassah) to enhance text analysis, as well as extensive reading to expand vocabulary and discourse comprehension. This study uses a qualitative descriptive method through a literature review consisting of Arabic linguistics books, modern literacy theories, empirical research findings, and scholarly journals on language education. The analysis reveals that the concept of al-qirā’ah encompasses three primary dimensions: (1) mechanical reading skills, including phonetic accuracy, reading fluency, and mastery of tajwīd rules when required; (2) comprehension skills, which include literal, inferential, evaluative, and applicative understanding of texts; and (3) interpretative and critical abilities, which are highly essential in academic settings. Research findings also indicate that universities typically emphasize intensive reading (Qirā’ah Mukhassafah) to train analytical reading skills, and extensive reading to broaden vocabulary and discourse mastery. Moreover, the integration of technology such as digital platforms, electronic dictionaries, interactive learning applications, and online text repositories greatly supports students in developing al-Qirā’ah independently. Student-centered learning approaches, scaffolding strategies, and project-based learning are also recommended as effective pedagogical practices in teaching al-Qirā’ah in modern higher education. Reading assessment is conducted not only through written examinations but also through portfolio evaluation, discourse analysis tasks, and academic presentations based on Arabic texts. Overall, this article is expected to contribute theoretically and practically to the development of more effective pedagogical models for teaching al-Qirā’ah in higher education. With a deeper conceptual understanding and the application of appropriate methodologies, Arabic reading instruction can become more adaptive, relevant, and responsive to the academic literacy needs of students in the modern era.